PERANCANGAN GAME EDUKASI BERBASIS AUGMENTED REALITY TENTANG SISTEM TATA SURYA UNTUK PESERTA DIDIK KELAS VI SDN 1 TEMPURAN TAHUN AJAR 2025/2026 MENGGUNAKAN GDEVELOP DAN ASSEMBLR EDU - Ady Nugroho, Wahyu; Hera Heru Sri Suryanti; Daryono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop an Augmented Reality (AR)-based educational game on the solar system as an interactive learning medium for sixth-grade students at SDN 1 Tempuran in the 2025/2026 academic year. The study was motivated by the limited availability of learning media capable of visualizing abstract solar system concepts, making it difficult for students to understand the material. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The game was developed using GDevelop and Assemblr Edu, followed by Black Box Testing, expert validation, and implementation involving 14 students. The results showed that the educational game functioned properly and achieved feasibility scores of 86% from media experts, 96% from subject matter experts, and 96% from teachers, all categorized as highly feasible. Student responses reached 100%, indicating a highly feasible category. Therefore, the AR-based educational game is suitable as a science learning medium for the solar system topic and has the potential to improve students' motivation, engagement, and understanding.